Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Siswa pada Materi Gaya dan Pemanfaatannya Kelas IV di SDN Leuwikidang - Nuraeni, Sinta; Taufik Saleh2, Yopa; Taufiq, Muhammad (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims to determine the effect of the Problem Based Learning model on student learning outcomes in style material and its use in class IV at SDN Leuwikidang. This research uses a quasi experimental design method with nonequivalent control group design. The research location is at SDN Leuwikidang. The subjects in this research were 39 students, all of whom were used as samples (total sampling), with an experimental class of 20 students and a control class of 19 students. Data collection techniques use observation, interviews and questionnaires. The instrument in this research is test questions (pretest and posttest) in the form of multiple choices. For data analysis techniques, use the normality test, homogeneity test, followed by hypothesis testing. Based on the results of the analysis and discussion of the research data, the results of the hypothesis test using the Mann Whitney test obtained a significance value or Asymp. Sig. (2-tailed) is 0.006, which means 0.006 < 0.05, then the H_o hypothesis is rejected. From these results, it can be concluded that the Problem Based Learning learning model has a significant influence on student learning outcomes in style material and its use in class IV at SDN Leuwikidang.